Development of Digital Learning Media to Strengthen Literacy and Numeracy in SDN 015 Rambah - Detri Amelia Chandra; Muslim Muslim; Firman Santosa; Ari Aprilia Dwiana; Santi Nurul Fianti (Computing and Education Technology Journal, 2026)
This study aimed to develop digital learning media to strengthen literacy and numeracy among fourth-grade students at SDN 015 Rambah and to examine its feasibility and effectiveness. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages, while the effectiveness test used a one-group pretest-posttest design. The limited trial involved 20 fourth-grade students, and product validation involved four validators, consisting of two material experts and two media experts. Data were collected through observation, interviews, validation sheets, and literacy-numeracy pre-test and post-test instruments covering information comprehension, numerical reasoning, contextual problem solving, and simple data interpretation. The data were analyzed descriptively and using the N-Gain index. The results showed that the developed media took the form of a lightweight, interactive, multi-device educational game application based on Progressive Web App (PWA) technology and was suitable for use under limited internet connectivity. The material expert validation score was 4.60 and the media expert validation score was 4.40, with an overall mean of 4.50 categorized as very feasible. The effectiveness test showed that students' mean score increased from 57.45 to 82.55, with an average N-Gain of 0.59 in the moderate category, indicating that the media was effective. The novelty of this study lies in the development of a PWA-based literacy and numeracy medium without a backend server that integrates concise materials, interactive exercises, immediate feedback, gamification, and local progress storage for elementary school settings with limited infrastructure. Therefore, the developed media is highly feasible and effective as a supporting tool for literacy and numeracy learning in elementary schools.